2012
DOI: 10.1097/bpb.0b013e3283504006
|View full text |Cite
|
Sign up to set email alerts
|

A collaborative public health approach to clubfoot intervention in 10 low-income and middle-income countries

Abstract: Untreated clubfoot has been acknowledged as a public health problem in low-income countries. In 2007-2009, a 10-country initiative was implemented by a collaboration of nongovernmental organizations and Ministries of Health to establish and strengthen national programmes for management of clubfoot using the Ponseti technique. Independent evaluation used quantitative data on programme outcomes and qualitative data from service providers and users. Overall, 110 clubfoot clinics were established, 634 practitioner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 8 publications
0
28
0
Order By: Relevance
“…There are several examples of successful and sustainable implementations of clubfoot programs in low-and middle income programs [5,8,22]. This could be a great solution in Indonesia, because at present there is no national program giving access to clubfoot care for the whole population in need.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several examples of successful and sustainable implementations of clubfoot programs in low-and middle income programs [5,8,22]. This could be a great solution in Indonesia, because at present there is no national program giving access to clubfoot care for the whole population in need.…”
Section: Discussionmentioning
confidence: 99%
“…With an estimated incidence of 1:1000 newborns, every year about 100,000-200,000 children are born with a clubfoot worldwide, from which about 80 % are in low-or middle-income countries [5,6]. The majority of these feet are not treated, leaving the child disabled for the rest of their life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Owen et al 5 have reported a larger series of 7705 cases, these were drawn from 10 different nations, with no single nation contributing >651 patients. The Bangladeshi clubfoot project has therefore secured an unprecedented rate of case ascertainment in its first 2 years.…”
Section: Project Organizationmentioning
confidence: 99%
“…The authors have completed surveys every 2 years since 2007, including as many treatment providers in LMIC as possible in order to monitor progress in ending disability caused by clubfoot. 9 …”
Section: Introductionmentioning
confidence: 99%